Pengaruh Modal Kerja, dan Likuiditas Terhadap Profitabilitas Perusahaan Manufaktur Sektor Industri Barang Konsumsi Di Bursa Efek Indonesia Periode 2018-2022 - Andika Indra Falim; Muhammad Andika; Dwi Aditya Rizky Saputra; Agustine Dwianika (Pusat Riset dan Inovasi Nasional, 2023)
Profitability measures how much a company's ability to generate profits. The size of the assets owned by the company in fulfilling obligations will affect the company's ability to earn profits. This study aims to determine the effect of working capital, fixed assets, and liquidity on profitability partially with a quantitative approach. The data analysis method used is a multiple regression analysis method processed using the SPSS program. The data used is secondary data, namely the financial statements of manufacturing companies and components obtained by accessing the official website of the Indonesia Stock Exchange (IDX). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The samples selected by the purposive sampling technique used in this study were 10 manufacturing companies in Indonesia. The results of this study indicate that simultaneously liquidity has a positive and significant effect on profitability, and working capital has an insignificant positive effect on profitability. This is important to consider by managers during profitability strategy implementation for manufactures company in Indonesia.